(untitled) (International Seven Journal of Health Research, 2026)
Breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) is a rare T-cell neoplasm mainly related to the use of textured breast implants. It usually presents as a late periprosthetic seroma, occurring years after implant surgery. We report the case of a 45-year-old patient with a history of augmentation mammoplasty with polyurethane implants who developed a persistent late seroma. After prolonged clinical and radiological follow-up, aspiration of the periprosthetic fluid revealed CD30-positive malignant cells, confirming the diagnosis of BIA-ALCL. The patient underwent bilateral breast explantation with complete capsulectomy, with no evidence of residual neoplasia in the surgical specimens. This case highlights the importance of clinical suspicion and cytopathological analysis of periprosthetic fluid in patients with late seroma, enabling early diagnosis and appropriate treatment, with a direct impact on prognosis.